Species Profiles of Some Useful Plants in Omo Biosphere Reserve in Nigeria - Obioh, Gloria I. B.; Isichei, Augustine O. (2014)
Ecological ethnobotany was conducted in Omo Biosphere Reserve, Nigeria in order to elucidate the basic ecological and cultural variables needed for the conservation and restoration of some useful utilised in the reserve. Permanent sample plots of 25m and 25m each were laid out randomly in four sites in the reserve. Data on both vegetation and soil in each site were collected by random sampling method. Quantitative Ethnobotany was carried out using the Participatory Rural Appraisal (PRA) technique. The target species were Carpolobia lutea G. Don, Dioscoreophyllum cumminsii (Stapf) Diels, Irvingia gabonensis (Aubry-Lecomb ex O'Rorke) Baill., Myrianthus arboreus P. Beauv., Sphenocentrum jollyanum Pierre, Spondias mombin L. Tetrapleura tetraptera Taub. and Xylopia aethiopica (Dunal) A. Rich. The species were selected because they are indigenous, non-timber and highly utilised in ethnomedicine and nutrition. A total of 132 woody species in 39 families were identified. Most of the target species were found only in the transition zone in very low densities of about two to five per hectare. Spondias mombin was found only in cultivated areas. The target species tolerate moderately acidic soils; majority flowered in the dry season and fruited during the rainy season. They were harvested from the wild and used in the treatment of many ailments including malaria, yellow fever, worms, cough, infertility, gonorrhea and diabetes. The inclusion of some of the species in conservation and restoration program in the reserve is suggested.